Variability in Andean nuña common beans (Phaseolus vulgaris, Fabaceae) - Tohme, Joseph M.; Toro Chica, Orlando; Vargas Daza, Jaime; Debouck, Daniel G. (Springer, 1995)
Nuñas are a group of common bean (Phaseolus vulgaris, Fabaceae) varieties, whose grains are consumed after toasting in their original Andean habitats. Nowadays, these varieties are restricted to certain parts of the highlands of Peru and Bolivia. Linguistic, ethnobotanical, and archaeological data suggest that they were grown in that zone during pre-Hispanic times. SDS-PAGE electrophoresis shows a wide range of phaseolin types among nuñas, many of which are present in sympatric wild forms. This paper discusses the possibility that nuñas resulted from an early and widely applied selection pressure during bean domestication in the Andes